EFEKTIVITAS PEMBELAJARAN BERDASARKAN MASALAH DALAM MENINGKATKAN AKTIVITAS DAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SMA - Sumarti (Jurnal Prinsip Pendidikan Matematika, 2019)
During teaching and learning process, the students tended to be passive and the class was dominated by the teacher. This situation made the students’ activity in learning became low as they just memorized the concepts instead of understood them. This research was aimed at improving students’ activity and ability in problem solving in Math through problem-based learning model.This was a classroom action research which was conducted in two cycles. The data of this research was collected through observation sheet and a test. The data gotten then was analyzed descriptively. The result of the research showed that the use of problem-based learning model could improve the first year students’ activity and ability of problem solving in Math at SMA Negeri 1 Pekanbaru. Students’ activities in completing LKS, asking questions to the teachers and peers, answering questions from the teachers and peers, presenting the result of group discussion and drawing a conclusion had been in very good category. In problem solving, the percentage of the students who had gained the minimum standard of achievement (KKM) improved from 61,30% in the first cycle into 82,14% in the second cycle.